Small changes in water levels and groundwater nutrients alter nitrogen and carbon processing in dune slack soils. (August 2016) - Rhymes, J.; Jones, L.; Wallace, H.; Jones, T.G.; Dunn, C.; Fenner, N.
Abstract: Dune slacks are biodiverse seasonal wetlands which experience considerable fluctuation in water table depth. They are under threat from eutrophication and lowered water tables due to climate change and water abstraction. The biological effects caused by the interactions of these pressures are poorly understood, particularly on soil processes. We used a mesocosm experiment and laboratory assays to study the impact of lowered water tables, groundwater nitrogen contamination, and their synergistic effects on soil microbial processes and greenhouse gas emissions. This study showed that just a 10 cm decrease in water table depth led to a reduction in denitrification and to a corresponding increase in soil nitrogen content. Meanwhile N2 O emissions occurred for longer durations within dune slack soils subject to higher concentrations of groundwater nitrogen contamination. The results from extracellular enzyme assays suggest that decomposition rates increase within drier soils shown by the increase in β-glucosidase activity, with further sensitivity to groundwater nitrogen contamination shown by the increase in phenol oxidase activity. Dune slack soils with a 10 cm lower water table had significantly lower CH4 emissions, nearly 5 times lower in the drier soils. Our findings demonstrate that dune slacks are sensitive to both small changes in groundwater levels and to groundwater nitrogen contamination. The biological impacts from lowered water tables are likely to be intensified where there is also groundwater nitrogen contamination. Highlights: Dune slacks are sensitive to small changes in water table and groundwater nitrogen. A 10 cm decrease in water table reduces denitrification activity. N2 O emissions occur for longer in soils with higher N groundwater concentrations. Decomposition rates increase and CH4 emissions decrease with lowered water tables. Soil processes are likely to be affected by climate change and eutrophication.